Ethical challenges in research involving children affected by armed conflict - von Denkowski, Cordula (Frontiers in Developmental Psychology, 2025)
Studies examining the impact of armed conflict on children's lives must confront a variety of ethical challenges, which may arise at any point in the research process and often in unexpected ways. Procedural ethics is therefore not sufficient, needing to be complemented by ethics in practice. Drawing on a critical analysis of power inequities in research carried out with conflict-affected children, this article proposes a reflexive, care-ethical approach to dealing with “ethically important moments” in research practice. It discusses how core principles of research ethics—such as informed consent, harm prevention and reciprocity—can be implemented when working with children in conflict settings as well as the respective challenges this may imply. It is argued that reflexivity based on care ethics is a collective practice involving not only researchers but also participants and other relevant actors alike.